Identification of pharmacogenomic markers of clinical efficacy in a dose-dense therapy regimen (R-CHOP14) in diffuse large B-cell lymphoma. Issue 9 (September 2014) - Nobili, Stefania; Napoli, Cristina; Puccini, Benedetta; Landini, Ida; Perrone, Gabriele; Brugia, Marco; Benelli, Gemma; Doria, Morena; Martelli, Maurizio; Finolezzi, Erica; Di Rocco, Alice; Del Fava, Emanuele; et al.
Abstract About 60% of patients with diffuse large B-cell lymphoma (DLBCL) may be cured by primary chemotherapy with an R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) regimen. Most of the rest will die of the disease, mainly due to the occurrence of tumor drug resistance. Many efforts have been made to explain the molecular mechanisms of drug resistance in patients with cancer, including those with DLBCL. This exploratory study was designed to correlate the mRNA expression levels of candidate genes mainly involved in the doxorubicin pathway (ABCB1, GSTP1, TOPO2α, BCL2, PKCβII) with the outcome of 54 patients with DLBCL undergoing a dose-dense R-CHOP regimen. After multivariate analysis, high GSTP1 (p = 0.003) and TOPO2α (p = 0.02) gene expressions were associated with shorter overall survival and progression-free survival, respectively, suggesting that these genes may represent an unfavorable prognostic factor in the case of R-CHOP treatment. These biomarkers may be useful for selecting patients eligible for personalized chemotherapy after validation in an independent set.